The Usage And Attitudes Towards Chatgpt Among The English Department Students In Samarinda - Selly Nur Maya Sari; Dr. Weningtyas Parama Iswari; Dra. Ida Wardani; Istanti Hermagustiana (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2025)
This research aims to examine the level of ChatGPT usage and the attitudes of English Department students in Samarinda toward its role in academic learning. The research is grounded in the rapid integration of artificial intelligence (AI) in higher education, particularly the increasing use of ChatGPT. A descriptive quantitative method was employed, using a validated questionnaire adapted from Sallam et al. (2024) which was distributed to 192 students from A University, B University, and C University. The data were analyzed using mean score calculations to determine the students’ level of usage and attitudes. The results showed that the majority of students (64.58%) used ChatGPT at a moderate level, indicating regular but not intensive engagement with the tool. In terms of attitudes, the majority of students (55.21%) demonstrated a neutral stance. Students generally found ChatGPT accessible and useful, although some expressed concerns related to academic integrity, data privacy, and overreliance on AI tools. In conclusion, English Department students in Samarinda are incorporating ChatGPT into their academic routines with both interest and caution. While they acknowledge its practical benefits, they also maintain a balanced perspective on its potential risks. These findings highlight the importance of promoting digital literacy and ethical awareness in the use of AI-based educational tools.